1988
DOI: 10.1159/000118424
|View full text |Cite
|
Sign up to set email alerts
|

Sydenham’s Chorea and Psychopathology

Abstract: Sydenham’s chorea is a movement disorder seen in rheumatic fever with basal ganglia pathology. This disorder has been associated with an increased frequency of psychopathology in both the acute choreiform stage and later in life. We conducted a prospective study of 29 subjects with Sydenham’s chorea and 29 age- and sex-matched controls. The total number of psychiatric symptoms 10 years after the initial contact was much greater in the study group than in controls (p < 0.001). Similarly, schizophrenia was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In one prospective case–control study by Wilcox and Nasrallah, evidence, spanning 10 years, from 29 individuals with Sydenham's chorea and 29 unaffected individuals was examined. The authors reported that individuals in the Sydenham's chorea group were 8.9 times more likely to develop schizophrenia than those in the comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…In one prospective case–control study by Wilcox and Nasrallah, evidence, spanning 10 years, from 29 individuals with Sydenham's chorea and 29 unaffected individuals was examined. The authors reported that individuals in the Sydenham's chorea group were 8.9 times more likely to develop schizophrenia than those in the comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…The interest in psychoses associated with RF continued throughout the 1900's [187-197]. People with a history of Sydenham chorea and/or rheumatic fever are at high risk for developing psychopathology later in life [198,199] with a relative risk for schizophrenia as high as 8.9 in a 10 year follow-up of 29 Sydenham patients [200]. There is a suggestion that the family members of Sydenham patients are also at higher risk for psychosis [201].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, generalized anxiety disorder was found at higher rates in first‐degree relatives of children with a history of rheumatic fever 16 . Psychosis was reported in one case; 17 however, retrospective studies in 369 individuals with psychosis have shown a higher than expected incidence of a history of Sydenham chorea, 18 and a prospective controlled study found that individuals with Sydenham chorea ( n =29) have a significantly higher risk of developing schizophrenia 19 …”
mentioning
confidence: 95%